Penerapan Pembelajaran Multimedia Interaktif Berbantuan Powtoon dalam Meningkatkan Hasil Belajar IPA Siswa Sekolah Dasar: Application of Interactive Multimedia Learning Assisted by Powtoon in Improving Elementary School Students' Science Learning Outcomes - Nur Afriani Amalia; Badruddin Kaddas; Ira Irviana (Madrasah Tsanawiyah DDI Cilellang, 2023)
The use of technology in elementary school education in Indonesia remains relatively low. However, students' interest in technology is increasing. This research aims to analyze efforts to improve students' science learning outcomes through the implementation of video-based interactive multimedia learning media using the Powtoon application. This type of research is Classroom Action Research (CAR). The research subjects were 25 fifth-grade elementary school students. Data collection techniques in this research are interviews, observations, tests, and documentation. The data in this research were analyzed using descriptive statistical analysis techniques. Based on the research conducted, the results obtained are: (1) The use of the Powtoon application can help teachers create multimedia in the form of interesting, unique, and interactive learning videos to support the success of the learning process in the classroom. (2) The data from the test results of Cycles I and II show an increase in students' science learning outcomes after participating in lessons that implemented video-based interactive multimedia created using the Powtoon application. This research has implications for the need for teachers to improve their professional competence in the use of technology as a learning media and tool. This must be done not only to make learning interesting and interactive, but also to make students accustomed to the use of technology in learning.